The impact of natural climate variability on air chemistry and regional air quality - Grewe, Volker (2005)
The modelling of the atmospheric composition on global scales has been significantly advanced during the last decade. A variety of processes are inherent in climate-chemistry models (CCMs), either resolved, parameterized or forced by boundary conditions. This ensures a better representation of the observed atmospheric composition and its variations, such as large scale climate phenomena (North-Atlantic Oscillation, El Nino/ La Nina, etc), volcanic eruptions, solar effects, etc. Additionally, feedbacks between processes are included, like the impact of ozone, methane, and other species on radiation and dynamics, dynamics on emissions (e.g. lightning), and many others. Dameris et al. (2005) present a troposphere-stratosphere simulation of the time period 1960 to 2000 using the CCM E39/C. This simulation includes observed sea-surface temperatures to account for effects like El Nino, and realistic planetary wave forcings, three major volcanic eruptions, the 11-year solar cycle, the Quasi-Biannual Oscillation (QBO), and varying emission of NOx and CFCs. The results show a good representation of the stratospheric and tropospheric dynamics, such as temperature trends, but also of the ozone layer, the development of the ozone hole, and tropospheric ozone in terms of composition and trend. The application of a number of diagnostics (e.g. marked ozone tracers) allows the separation of the impact of various processes/emissions on tropospheric ozone. The simulated Northern Hemisphere tropospheric ozone budget is not only dominated by nitrogen oxide emissions and other ozone pre-cursors, but also by changes of the stratospheric ozone budget and the its flux into the troposphere, which tends to reduce the positive trend in ozone due to emissions from industry and traffic during the late 80s and early 90s. Although the horizontal resolution is rather coarse in comparison to regional models, such kind of simulations provide useful and necessary information on the impact of large-scale processes and inter-annual / decadal ...